2019
DOI: 10.7759/cureus.4843
|View full text |Cite
|
Sign up to set email alerts
|

Resident Physicians are at Increased Risk for Dangerous Driving after Extended-duration Work Shifts: A Systematic Review

Abstract: Background: Resident physicians often work longer than 24 consecutive hours with little or no sleep. A systematic review of the literature was conducted to investigate the risk of resident physician motor vehicle collisions (MVC), and dangerous driving, after extended-duration work shifts (EDWS). Material and methods: A keyword search was performed for original research articles evaluating any aspect of driving safety following EDWS for the resident physician population. Two authors independently re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 27 publications
3
18
0
1
Order By: Relevance
“…Our study, showed that NF system had signi cant improvement in these three aspects. Several studies showed the traditional on-call system is associated with loss of sleep and fatigue which is like our study results [2][3]. Furthermore, the 24 hour on-call system shown to negatively affect physical function and memory in our pediatric residents and neurosurgery residents in another study [15].…”
Section: Discussion and Literature Reviewsupporting
confidence: 83%
See 3 more Smart Citations
“…Our study, showed that NF system had signi cant improvement in these three aspects. Several studies showed the traditional on-call system is associated with loss of sleep and fatigue which is like our study results [2][3]. Furthermore, the 24 hour on-call system shown to negatively affect physical function and memory in our pediatric residents and neurosurgery residents in another study [15].…”
Section: Discussion and Literature Reviewsupporting
confidence: 83%
“…The limitation of our study were lack of assessment regarding the risk of motor vehicle accidents and near-miss driving events that could be related with loss of sleep and fatigue during long-time shifts [2][3]13]. Also, we did not evaluate the cognitive function which is another limitation [15].…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…There is risk of acute harm to practitioners. A systematic review demonstrated an elevated risk for road traffic incidents in doctors after extended shift work [16]. The largest study included in the review followed 2500 junior doctors in the USA over a year and found that those working an extended duration shift (>24 h) were 2.3 times more likely to have a motor vehicle car crash, and 5.9 times more likely to have a near miss, than following a non-extended duration shift [17].…”
Section: The Impact Of Extended Shifts On Safetymentioning
confidence: 99%